UPAYA PERLINDUNGAN LINGKUNGAN PERSPEKTIF KONSTITUSI DAN PENDIDIKAN KEWARGANEGARAAN - Feriandi, yoga Ardian (Universitas Muhammadiyah Ponorogo, 2018)
The purpose of writing this article is to look at the environmental protection efforts undertaken by the government from the perspective of the constitution and education of Citizenship. The method used in the writing of this article is Library Research, which collects data from scientific articles, research reports or other things relevant to the topic. From the results of this study can be seen that the actual environmental protection already exists in the Indonesian Constitution that is in article 28H paragraph 1 and article 33 paragraph 4 of the 1945 Constitution. While the education of citizenship protection can be seen from efforts to awaken the responsibility of citizens related to environmental sustainability and apply the 18 character values in KDP learning. There are also adiwiyata programs integrated in PPKn subjects.